Optimization of oil-based liquid lipstick formula from sesame seed oil (Sesamum indicum L.) and antibacterial activity test against Staphylococcus aureus - Miksusanti, Miksusanti; Wijaya, Dina Permata; Kovalina, Yosi; Wardana, Mutia Sari; Herlina, Herlina (Faculty of Pharmacy, Universitas Pancasila, 2025)
Liquid lipstick is a type of lip color cosmetic that consumers highly favor. However, repeated use of liquid lipstick can promote the growth of Staphylococcus aureus (S. aureus) bacteria. The formulation of liquid lipstick involves several components, including a mixture of wax, oil, and other additives. Sesame seed oil (Sesamum indicum L.), incorporated into the formulation, serves as both a base and preservative due to its fatty acid content, which is expected to inhibit the growth of S. aureus bacteria. Microcrystalline wax is added to achieve a good texture and enhance the adhesion properties of the formulation. This study aimed to determine the optimum formula and evaluate the antibacterial activity of the liquid lipstick formulation. The formula was developed using a 2² factorial design method, with sesame seed oil and microcrystalline wax as variables. The optimum formula was analyzed using Design Expert® 13 software based on parameters such as viscosity, spreadability, and adhesion. The final optimum formula consisted of 70% sesame seed oil and 5% microcrystalline wax. The formulation demonstrated good stability during the cycling test, maintaining red color, vanilla and sesame-like aroma, liquid texture, and pH 5. The viscosity was 11797.51 cP, the spreadability was 6.06 cm, and the adhesion time was 64 seconds. Antibacterial activity, assessed using the disk diffusion method, yielded an inhibition zone diameter of 15±1.322 mm, indicating a strong inhibition zone. Based on the research findings, it was concluded that the optimum sesame seed oil-based liquid lipstick formula exhibited good product characteristics, stability, and strong antibacterial activity.